2008
DOI: 10.1111/j.1745-459x.2008.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Hidden and False “Preferences” on the Structured 9‐point Hedonic Scale

Abstract: An unspecified number of consumers who used a 9‐point hedonic scale were frustrated because they could not express preferences for products with the same ratings. Accordingly, consumers were required to rate samples of yogurt on a 9‐point structured hedonic scale. Consumers were able to express preference judgments because the testing was performed one‐on‐one with the experimenter. Thus, it was possible to determine the proportion of consumers who had given the same hedonic response to yogurts but still had pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Nevertheless, this does not pose problem for measuring relative (ordinal) preferences among stimuli, which was its intended purpose. Second, due to its limited number of response categories, the 9-point hedonic scale offers little freedom for subjects to express the full range of their hedonic experiences (Marchisano et al, 2003;Villanueva & Da Silva, 2009;Villegas-Ruiz, Angulo, & O'Mahony, 2008). Third, because of both its small number of available categories and the general tendency of subjects to avoid using extreme categories (Hollingworth, 1910;Moskowitz, 1982;O'Mahony, 1982), the scale is highly vulnerable to ceiling effects (Schutz & Cardello, 2001;Stevens & Galanter, 1957), one of the context effects that was described above (Section 2.3.4).…”
Section: Limitationsmentioning
confidence: 99%
“…Nevertheless, this does not pose problem for measuring relative (ordinal) preferences among stimuli, which was its intended purpose. Second, due to its limited number of response categories, the 9-point hedonic scale offers little freedom for subjects to express the full range of their hedonic experiences (Marchisano et al, 2003;Villanueva & Da Silva, 2009;Villegas-Ruiz, Angulo, & O'Mahony, 2008). Third, because of both its small number of available categories and the general tendency of subjects to avoid using extreme categories (Hollingworth, 1910;Moskowitz, 1982;O'Mahony, 1982), the scale is highly vulnerable to ceiling effects (Schutz & Cardello, 2001;Stevens & Galanter, 1957), one of the context effects that was described above (Section 2.3.4).…”
Section: Limitationsmentioning
confidence: 99%
“…They reported that ‘participants were frustrated when they liked the two samples equally, but had a preference for one, and could not indicate this on the response sheet.’ However, they did not report the proportion of participants who had made this complaint. Villegas‐Ruiz et al investigated this, using three strawberry yogurts and the same ‘words only’ scale. Of their 116 consumers, they noted that 32 (28%) gave identical responses for two of the yogurts, while one consumer gave identical responses for all three.…”
Section: Some Problems With the 9‐point Hedonic Scalementioning
confidence: 99%
“…Consequently, the scale produces only ordinal-or, at best, interval-level data, as opposed to ratio-level data (Stevens, 1951). Second, because it is a category scale, the 9-point hedonic scale offers little freedom for consumers to express their preference among products (Marchisano et al, 2003;Villegas-Ruiz, Angulo, & O'Mahony, 2008). In addition, because there are only nine choices available and also because consumers often avoid using extreme response categories (Hollingworth, 1910;Moskowitz, 1982;O'Mahony, 1982), the scale is highly vulnerable to the ceiling effects.…”
Section: Introductionmentioning
confidence: 98%